2017
DOI: 10.1007/s10867-016-9440-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics exploration of the binding mechanism and properties of single-walled carbon nanotube to WT and mutant VP35 FBP region of Ebola virus

Abstract: VP35 of Ebola viruses (EBOVs) is an attractive potential target because of its multifunction. All-atom molecular dynamics (MD) simulations and Molecular Mechanics Generalized Born surface area (MM/GBSA) energy calculations are performed to investigate the single-walled carbon nanotube (SWCNT) as an inhibitor in wild-type (WT) VP35 as well as in three primary mutants (K248A, I295A, and K248A/I295A) through docking the SWCNT in the first basic patch (FBP) of VP35. The SWCNTs of all the four systems effectively b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…However, the actual importance of this amino acid residue had not been evaluated in biological assays in vitro. In this study, we provide direct evidence that P293 is important for both polymerase cofactor function and suppression of IFN production, supporting the previous in silico studies that predicted the functional importance of this amino acid position [31][32][33]. Interestingly, the VP35 functions were impaired even by the P293 mutants with amino acid substitutions that had little effect on the patch #3 hydrophobicity (Figure 2).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the actual importance of this amino acid residue had not been evaluated in biological assays in vitro. In this study, we provide direct evidence that P293 is important for both polymerase cofactor function and suppression of IFN production, supporting the previous in silico studies that predicted the functional importance of this amino acid position [31][32][33]. Interestingly, the VP35 functions were impaired even by the P293 mutants with amino acid substitutions that had little effect on the patch #3 hydrophobicity (Figure 2).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we have shown for the first time that P293 of VP35 contributes to polymerase cofactor activity and IFN-β suppression. Using computer analyses, the P293 residue has been predicted to be important for the interaction with small molecule compounds that may potentially inhibit VP35 functions [31][32][33]. However, the actual importance of this amino acid residue had not been evaluated in biological assays in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the binding energy between lysozyme and Gd@C 60 and their components, we carried out a MM-GBSA analysis of the trajectory. This methodology has provided valuable information to estimate the interaction between proteins and carbon nanomaterials. …”
Section: Results and Discussionmentioning
confidence: 99%
“…In the third step, the system was minimized at a constant temperature of 300 K and a constant pressure of 1 atm for another 50 ps. In the last step, the whole system was equilibrated at the NPT ensemble for 500 ps without any restraints . In the MD simulation, the temperature was set to 300 K, and periodic boundary condition was applied to all dimensions.…”
Section: Methodsmentioning
confidence: 99%
“…In the last step, the whole system was equilibrated at the NPT ensemble for 500 ps without any restraints. 29 In the MD simulation, the temperature was set to 300 K, and periodic boundary condition was applied to all dimensions. The dsRNA-free and dsRNA-binding trajectories were run for 520 ns (WT-free), 300 ns (R312A-free), 250 ns (R322A-free), 220 ns (K339Afree), 270 ns (R312A/R322A-free), 380 ns (WT-dsRNA), 410 ns (R312A-dsRNA), 620 ns (R322A-dsRNA), 300 ns (K339A-dsRNA), and 620 ns (R312A/R322A-dsRNA), respectively, when all the systems have achieved equilibrium.…”
Section: Molecular Dynamics (Md) Simulationmentioning
confidence: 99%